The effects of audit risk and information importance on auditor memory during working paper review. - Sprinkle, Geoffrey B.; Tubbs, Richard M. (The Accounting Review, 1998)
Prior research on auditors' memory for evidence encountered during working paper review suggests that auditors commit memory errors that could inhibit audit efficiency and effectiveness. The current study extends this line of research by examining whether two prominent features of the auditing environment. The current study extends this line of research by examination whether two prominent features of the auditing environment, audit risk and information importance, affect the accuracy of auditors' memory and auditors' memory and author's willingness to rely on memory. These issues were examined in an experiment in which auditors were required to review two working-paper areas (accounts) and, 24 hours later, recognize if information items had been present in the working papers and express how willing they would be to rely on their memory for each item. The results indicate that (1) the accuracy of auditors' memories is positively related to the level of audit risk of the area and the degree of importance of an information item within the area; (2) the auditors' willingness to rely on memory is negatively related to the degree of information importance but not related to the level of audit risk of the area; and (3) the auditors' likelihood of referring back to the working papers is negatively related to the accuracy of auditors' memories, and this negative relationship increase with the degree of information importance. Collectively, these results suggest that audit risk and information importance altered auditor's cognitive activities during the review process in a manner that contributes to the effectiveness (e.g., better memory for more consequential evidence) and efficiency (e.g., less verification more strongly remembered and less consequential evidence) of the audit.